Sex differences in mechanisms of head impacts in collegiate soccer athletes. (April 2020) - Saunders, Tabitha D.; Le, Rachel K.; Breedlove, Katherine M.; Bradney, Debbie A.; Bowman, Thomas G.
Abstract: Background: There has been growing interest in head impacts related to sports participation due to potential long- and short-term consequences of head injuries. Our purpose was to compare head impact magnitude and frequency between men's and women's intercollegiate soccer players based on head impact mechanism. Methods: 28 collegiate soccer players (16 women: age = 19.94 (1.06) years, height = 163.75 (5.15) cm, mass = 61.21 (5.09) kg; 12 men: age = 20.25 (1.14) years, height = 180.34 (6.03) cm, mass = 74.09 (9.32) kg) wore xPatch (X2 Biosystems, Seattle, WA) head impact sensors. Each practice and game was video recorded in order to confirm head impacts. The independent variable was impact mechanism (head to head, head to body (other than head), head to ground, ball to head, goal to head, and combination). Sensors collected linear and rotational accelerations and frequency of head impacts per 1000 athlete exposures. Findings: Men were more likely to sustain head impacts than women (IRR = 1.74, CI95  = 1.59–1.92). The highest head impact incidence rate for men was head to body (IR = 611.68, CI95  = 553.11–670.25) while the highest impact incidence rate for women was ball to head (IR = 302.29, CI95  = 270.93–333.64). The interaction between sex and mechanism was significant for rotational accelerations (F4, 1720  = 3.757, P  = .005, ω 2  = 0.013) but not for linear accelerations (F4, 1720  = 0.680, P  = .606, ω 2  < 0.001, 1 − β = 0.223). Interpretation: To reduce the frequency of head impacts in men, perhaps rules governing player to player contact should be more strictly enforced as these data confirm frequent player-to-head contact during soccer practices and games. Prevention efforts for women should be focused on limiting the amount of purposeful heading (planned contact between the head and ball) occurring during play especially since these impacts had higher magnitudes compared to men. Highlights: These data confirm frequent player-to-head contact during soccer practices and games, especially for men. Men were 1.7 times more likely to sustain head impacts than women. Head to body and ball to head were most common impact mechanisms for men and women, respectively. Women sustained ball to head impacts with higher magnitudes compared to men.